Análise da influência do teor de lignina de fibras vegetais nas características mecânicas e física do composto cimentício - Danno, Henrique Shiguemitsu (Universidade Federal de São Carlos, 2021)
Civil construction is an industrial sector that consumes natural resources. To supply this demand, this sector has sought to use alternative sources of material and with positive mechanical performance. This market is looking for new sources of fibers, since asbestos, the most commonly used material, has restrictive restrictions regarding legislation, in addition to steel and polymers that cause negative impacts on its extraction and processing. Limit to Brazil's agricultural potential, vegetable fibers are natural and renewable sources, and can be applied in fiber cement. However, its mechanical performance can vary according to the lignin content. This research project aimed to analyze the influence that the lignin content of vegetable fiber can have on the mechanical strength of fiber concrete, looking for a possibility of establishing a relationship between these two factors in order to predict the feasibility of its use in civil construction. For this research work, there were two types of vegetable fiber with different lignin contents (soybean and bamboo). Vegetable fibers were prepared with drying treatment to remove internal moisture. Subsequently, its critical length was determined by a pull-out test and cut to be incorporated into the fiber cement. The test pieces were molded in body percentages of 0, 2, 6 and 10%, and cured according to NBR 5738 and NBR 5739, respectively. Mechanical strength tests followed NBR 5739. Mechanical strength was provided based on NBR 12655, and the Impact Test followed NBR 13818/1997. It can be demanded that there is a direct relationship between the lignin content and the increase in strength and energy absorption of the concrete. The recommended model with the best results was with an addition of 2% Bamboo fiber.
Analysis of the influence of plant fiber lignin content on the physical and mechanical characteristics of the cementitious composite
Keywords: Material alternativo de construção; Concreto; Fibras vegetais; Teor de lignina; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL